2014
DOI: 10.1007/s11356-014-3204-1
|View full text |Cite
|
Sign up to set email alerts
|

Rhizofiltration of lead using an aromatic medicinal plant Plectranthus amboinicus cultured in a hydroponic nutrient film technique (NFT) system

Abstract: Heavy metal contamination of water bodies and groundwater is a major concern of the modern world. Rhizofiltration--the use of plant root system to remove/extract pollutants from wastewater--has proven advantages over conventional methods of treatment. However, commercialization of this in situ remediation technology requires a better understanding of plant-metal interactions especially on the ability of different plant species to accumulate metals at different parts of the plant system which is critical for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In the present study, Pb was mainly accumulated in roots of both plants ( Table 2), implying that this metal was limited to the apoplastic space of the cortex and its loading into the vascular cylinder was effectively stopped by the endodermal Casparian strips of the root. Thus, Pb was often found to be accumulated in or beyond the endodermis (Jones et al 1973, Ignatius et al 2014. Our results were in agreement with previous studies (Michalak and Wierzbicka 1998, Antosiewicz et al 2003, Sharma and Dubey 2005.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, Pb was mainly accumulated in roots of both plants ( Table 2), implying that this metal was limited to the apoplastic space of the cortex and its loading into the vascular cylinder was effectively stopped by the endodermal Casparian strips of the root. Thus, Pb was often found to be accumulated in or beyond the endodermis (Jones et al 1973, Ignatius et al 2014. Our results were in agreement with previous studies (Michalak and Wierzbicka 1998, Antosiewicz et al 2003, Sharma and Dubey 2005.…”
Section: Discussionsupporting
confidence: 93%
“…Ignatius et al . (2014) used Mexican mint in hydroponic systems type NFT to evaluate the rhizofiltration of Pb at different concentrations. The study demonstrated that the plants have the capacity to accumulate Pb in the roots, without translocating it to stems or leaves.…”
Section: Uses For Hydroponic Systemsmentioning
confidence: 99%
“…Plants with large fibrous root systems removed markedly more metals than did plants with coarser roots (Table 2). Larger root systems have greater surface areas, which absorb and adsorb more metals (Li et al 2015); this is especially important for Pb, which readily binds to organic matter such as roots (Ignatius et al 2014). The lack of restricting tissue, such as exodermis, in young fine roots enables high absorption to the apoplast.…”
Section: Influence Of Roots and Belowground Partsmentioning
confidence: 99%